WORKS FOR PIANO IN THE WORK OF COMPOSER RUSTAM ABDULLAYEV (International journal of artificial intelligence, 2025)
Rustam Abdullaev, ijod, miniatyura, sikl, xalq musiqasi, ritm, an'ana. Annotation: There are musical works for various musical instruments. Composers often turn to the piano, this is especially true now, in our time, when beauty is valued in miniatures. This article will examine the works of small form for piano by Rustam Abdullaev - the plays “Alla”, “Page from Life” and “Scherzo”.